Vitamin D supplementation and total cancer incidence and mortality: a meta-analysis of randomized controlled trials - Keum, N; Lee, D H; Greenwood, D C; Manson, J E; Giovannucci, E (Annals of oncology, 2019)
Previous meta-analyses of randomized controlled trials (RCTs) of vitamin D supplementation and total cancer incidence and mortality found inconsistent results, and most included trials administered generally low doses of vitamin D (≤1100 IU/day). We updated the meta-analysis by incorporating recent RCTs that have tested higher doses of vitamin D supplements. PubMed and Embase were searched from the inception to November 2018. Summary relative risks (RRs) and 95% confidence intervals (CIs) were estimated using a random-effects model. For total cancer incidence, 10 trials were included [6537 cases; 3-10 years of follow-up; 54-135 nmol/l of attained levels of circulating 25(OH) vitamin D [25(OH)D] in the intervention group]. The summary RR was 0.98 (95% CI, 0.93-1.03; P = 0.42; I2 = 0%). The results remained null across subgroups tested, including even when attained 25(OH)D levels exceeded 100 nmol/l (RR, 0.95; 95% CI, 0.83-1.09; P = 0.48; I2 = 26%). For total cancer mortality, five trials were included [1591 deaths; 3-10 years of follow-up; 54-135 nmol/l of attained levels of circulating 25(OH)D in the intervention group]. The summary RR was 0.87 (95% CI, 0.79-0.96; P = 0.005; I2 = 0%), which was largely attributable to interventions with daily dosing (as opposed to infrequent bolus dosing). No statistically significant heterogeneity was observed by attained levels of circulating 25(OH)D (Pheterogeneity = 0.83), with RR being 0.88 (95% CI, 0.78-0.98; P = 0.02; I2 = 0%) for ≤100 nmol/l and 0.85 (95% CI, 0.70-1.03; P = 0.11; I2 = 0%) for >100 nmol/l. In an updated meta-analysis of RCTs, vitamin D supplementation significantly reduced total cancer mortality but did not reduce total cancer incidence.